Husserl’s Phenomenology: A Study On The Construction Of The Meaning Of Tax, Zakat And Tithe - Azmala, 'Ilya; Triyuwono, Iwan; Djamhuri, Ali (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
The purpose of this research was to find the meaning or interpret what has been conveyed by taxpayers’ income tax 21, profession zakat payers and tithers. The informant selection purposive sampling method was used. This research applied an interpretive paradigm with a Husserl’s transcendental phenomenology approach. Moreover, the unit of analysis used in transcendental phenomenology was intentionality, noema and noesis, intuition and intersubjectivity. Regarding the data analysis technique in this study were through the stages such as bracketing, horizonalization, cluster of meaning, textural description, structural description and composite description (synthesis of meaning and essences). Moreover, the deriving results of the research obtained four meanings of tax, zakat and tithe. It can be concluded from the informant's experience, spiritual meaning as a manifestation of obedience to God, physical meaning as an act according to the rule, mental meaning as forming mental health, and nationalist meaning as a form of strategy against phobia.